Phylogenetic analysis of sandflies populations using cytochrome b (mtCytb) gene and identification of Leishmania DNA within infected sanflies, from the city of Najaf, Iraq - Al-Huchaimi, Sundus Nsaif; Al-Nafakh, Rana Talib; Al-Khafaji, Zaytoon AbdulridaIghewish; Amad, Noor; Mahmood, Thikra A.; Bedri, Sumaya; Bustan, Yahya (Journal of Contemporary Medical Sciences, 2018)
Objectives: Sandflies are a major public health concern in various parts of the world. The aim of this study was to identify the species and strain of sandflies, using molecular methods. Methods: Sandflies were collected from January to October 2017, in 16 rural areas in the province of Najaf AL-Ashraf, Iraq. PCR technique was performed for detection of mitochondrial cytochrome b (mtCytb) gene in Phlebotomus papatasi (P. papatasi), Phlebotomus sergenti (P. sergenti), and Sergentomyia sintoni (S. sintoni). DNA sequencing method was performed for confirmatory identification of P. papatasi, P. sergenti and S. sintoni from local isolates based on mtCytb, using phylogenetic tree analysis (MEGA.6) and NCBI–BLAST multiple sequence alignment tool. Results: Morphological identification of sandflies shows that all specimens were categorized into two genera with 3 species, Phlebotomus and Sergentomyia. Leishmania DNA was detected in 16 pools, all were infected with L. major, 8 of them infected with L. tropica. Sequencing and phylogenetic inference analysis confirmed that the local P. papatasi isolates were demonstrated to be closely related to the NCBI, P. papatasi reference sequence (AF161214.1), the local P. sergenti isolates showed high similarity with the NCBI, P. sergenti sequence (AF161216.1), and the local S. sintoni isolates showed high homology with the NCBI, S. sintoni sequence (EU159507.1). Conclusions: P. papatasi, P. sergenti and S. sintoni were the genotypes that has a high prevalence in the city of Najaf. No previous data were found in this regard. The present study contributes to a better understanding of the molecular epidemiology of this parasite.